(3GdJegjO dbhGYO GdJhMjOs - (3ejehf Hf eMeO Hf eMeO Hf eYHO Hf ecMhd, CHh GdeYjf GdfSaj GdMfaj,J (B508 (3g` s
(3ChdgG (B:s
(3CfJ CcJH dg YbjOI ef Sda ef eTGjN Cgd GdSfI hGdLeGYI , hCHjf eG cGfhG Ydjg ef GdePgH GdMejO ai Yde GdJhMjO s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B341 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B66s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B122 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B484s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds